Conflict Management through Neuro-Linguistic Programming (NLP) Approach - Sakinatunnafsih; M. Surya Bhaskara; Ichsan Malik (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Conflict is an inevitable part of life. Conflict management is an essential part of the success to manage interacting issues with others, both in professional and personal environments. One highly suitable method for conflict management is Neuro-Linguistic Programming (NLP) approach, which views human language and behavior as learnable and changeable to achieve specific goals, including resolving conflicts. NLP provides several techniques and methods that can help someone manage conflict more effectively, such as managing emotions, identifying and understanding differences in perception, and building better relationships. This study aims to test the effectiveness of the NLP approach in conflict management through a case study that is researched using a qualitative approach with interview techniques to collect data from sources involved directly or indirectly in the conflict that occurred. The results of the study show that the NLP approach is considered effective in social conflict management. NLP techniques in recognizing communication patterns through Linguistic Model (Meta Model and Milton Model) using Chunking techniques can help manage conflict and improve relationships between conflicting parties.  This study also found that the Chunking method in NLP is very suitable for resolving conflicts at the micro level, while for conflict resolution at the meso and macro levels, the Chunking approach can be combined with other NLP approaches such as ‘ecology checking’, and ‘future pacing’. Overall, conflict management using NLP can help improve someone's ability, especially for conflict resolvers and mediators, to manage conflicts more effectively and help conflicting parties find fair and equal solutions.